No. 1. The World on an Equatorial Projection: Map of the Eastern & Western Hemispheres. - Mitchell, S. Augustus (Samuel Augustus), 1792-1868 (S. Augustus Mitchell, 1852)
This sheet includes three separate maps. At the top and bottom of the page, there are circular, connected hemisphere maps showing the east and west hemispheres, and north and south hemispheres respectively. A note at the head of the page says, "The track laid down on Map no. 1, is that of the U.S. Exploring Expedition, in the voyage round the world performed in the years 1838, 39, 40, 41 and 42. The arrows indicate the directions sailed." Continents are labeled and shaded in color. Geographic features are marked (with relief shown by hachures, spot heights, and pictorially). In the center of the page, there is a map showing recent discoveries in Antarctica with text regarding the expeditions.